2016
DOI: 10.1111/jfcj.12060
|View full text |Cite
|
Sign up to set email alerts
|

Family Drug Treatment Courts As Comprehensive Service Models: Cost Considerations

Abstract: Literature on family drug treatment courts (FDTCs) suggests that parental participation in these courts is associated with improved substance abuse treatment and child welfare system outcomes. Despite these beneficial outcomes, FDTCs serve only 7‐10% of eligible child welfare involved families. As part of a FDTC evaluation, this FDTC site sought to provide stakeholders with information about costs and benefits. Considering the program costs alongside the cost avoidance from reduced time in foster care, this an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Child welfare opinion leaders have identified evidence‐based behavioural parenting interventions (EBPIs) as a critical strategy for addressing maltreatment and improving child welfare outcomes (Barth et al, ; Horwitz, Chamberlain, Landsverk, & Mullican, ), including for families affected by substance use (Barth, ). Brook and colleagues have also shown that a group‐based EBPI promotes reunification among parents affected by substances with children in foster care (Brook, Akin, Lloyd, Johnson‐Motoyama, & Yan, ; Brook, Akin, Lloyd, & Yan, ; Brook, McDonald, & Yan, ). Despite efforts to expand EBPIs to child welfare, a formidable barrier is parental engagement and service completion as an intervention has little chance of improving outcomes unless families engage in the intervention (Berliner et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Child welfare opinion leaders have identified evidence‐based behavioural parenting interventions (EBPIs) as a critical strategy for addressing maltreatment and improving child welfare outcomes (Barth et al, ; Horwitz, Chamberlain, Landsverk, & Mullican, ), including for families affected by substance use (Barth, ). Brook and colleagues have also shown that a group‐based EBPI promotes reunification among parents affected by substances with children in foster care (Brook, Akin, Lloyd, Johnson‐Motoyama, & Yan, ; Brook, Akin, Lloyd, & Yan, ; Brook, McDonald, & Yan, ). Despite efforts to expand EBPIs to child welfare, a formidable barrier is parental engagement and service completion as an intervention has little chance of improving outcomes unless families engage in the intervention (Berliner et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has suggested that low levels of household income, institutional racism, and high rates of unemployment place families at disproportionate risk for experiencing family traumas (Merrick et al, 2018). Families who have experienced such traumas have unique needs stemming from their conditions prior to separation, the subsequent absence of family members, and the transitions related to reunification (Brook, Akin, Lloyd, Johnson‐Motoyama, & Yan, 2016). Exposure to adverse childhood experiences such as the aforementioned can have negative additive effects that impact social and emotional functioning across the life span (Larkin, Shields, & Anda, 2012).…”
Section: Trauma and Family Literacymentioning
confidence: 99%
“…In Australia and England, permanent loss of the child at the end of the court process is considered both sufficient incentive and punishment. The principles of problem-solving courts have been articulated (Brook, Akin, Lloyd, Johnson-Motoyama & Yan, 2016;Choi, 2012) that result in special attention to the process as well as the goals.…”
Section: Fdtcs-a Member Of the Family Of Problem-solving Courtsmentioning
confidence: 99%